2021
DOI: 10.1016/s2213-2600(21)00383-0
|View full text |Cite|
|
Sign up to set email alerts
|

Physical, cognitive, and mental health impacts of COVID-19 after hospitalisation (PHOSP-COVID): a UK multicentre, prospective cohort study

Abstract: Background The impact of COVID-19 on physical and mental health and employment after hospitalisation with acute disease is not well understood. The aim of this study was to determine the effects of COVID-19-related hospitalisation on health and employment, to identify factors associated with recovery, and to describe recovery phenotypes. MethodsThe Post-hospitalisation COVID-19 study (PHOSP-COVID) is a multicentre, long-term follow-up study of adults (aged ≥18 years) discharged from hospital in the UK with a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
462
2
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(558 citation statements)
references
References 30 publications
38
462
2
10
Order By: Relevance
“…Evans et al. 8 evaluated 1170 patients, discharged from the hospital following treatment for COVID-19 and identified 4 clusters of patients suffering from PCS, according to mental and physical impairment. They analysed plasma CRP according to the clusters and found that patients included in clusters 1 and 2, with very severe and severe impairment, showed frequencies of CRP >1.0 mg/dL of 16.5% and 18%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans et al. 8 evaluated 1170 patients, discharged from the hospital following treatment for COVID-19 and identified 4 clusters of patients suffering from PCS, according to mental and physical impairment. They analysed plasma CRP according to the clusters and found that patients included in clusters 1 and 2, with very severe and severe impairment, showed frequencies of CRP >1.0 mg/dL of 16.5% and 18%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, available data on biomarkers in PCS are very scarce 18 , poorly systematised and with conflicting results. Elevation of C-reactive protein (CRP) serum levels has been reported 8 , while other studies found no association 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating the prevalence of persistent symptoms is not easy due to differences in populations and methods used, and some studies reporting mixed data from hospitalized and non-hospitalized patients. Estimates therefore vary greatly across different studies [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The SBQ™-LC's conceptual framework was developed from systematic literature reviews of Long COVID symptoms [4,25]. Existing symptom measures (n = 6) with good face validity in the context of Long COVID were reviewed to establish whether a new PRO instrument of symptom burden was needed [26][27][28][29][30][31]. When mapped to the conceptual framework, symptom coverage of these measures ranged from 25.0% to 64.1% (mean = 42.4% SD 16.8).…”
Section: Symptom Coverage and Existing Prosmentioning
confidence: 99%